1998
DOI: 10.1183/09031936.98.11061294
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 0.2 ppm ozone on biomarkers of inflammation in bronchoalveolar lavage fluid and bronchial mucosa of healthy subjects

Abstract: Several studies evaluating the effects of ozone on healthy as well as asthmatic subjects have shown that short-term exposure to 0.08-0.40 parts per million (ppm) ozone impairs lung function and induces an acute inflammatory response [1][2][3]. These studies have reported an influx of polymorphonuclear neutrophils (PMNs) and secretion of interleukins (IL)-6 and 8, granulocyte macrophage colony stimulating factor (GM-CSF), total protein, albumin, fibronectin and complement C3a [1][2][3].Endothelial adhesion mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
72
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 25 publications
2
72
1
Order By: Relevance
“…35,36 ROS appear to directly stimulate the release of histamine from mast cells and mucus secretion from airway epithelial cells. 37 Increased ROS release may directly result in oxidative damage to epithelial cells and cell shedding. 29 Previous studies have suggested that ROS may lead to endothelial barrier dysfunction, with subsequent increased permeability to fluid, macromolecules, and inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…35,36 ROS appear to directly stimulate the release of histamine from mast cells and mucus secretion from airway epithelial cells. 37 Increased ROS release may directly result in oxidative damage to epithelial cells and cell shedding. 29 Previous studies have suggested that ROS may lead to endothelial barrier dysfunction, with subsequent increased permeability to fluid, macromolecules, and inflammatory cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is an urgent unmet need for new lung disease treatments. For ethical reasons, studies in humans are restricted to some baseline investigations and a limited range of in vivo challenges (e.g., allergen, ozone, exercise, diesel exhaust) used in conjunction with morphological assessment of tissue biopsies or cells obtained by bronchoalveolar lavage (BAL) (Krishna et al, 1998;Salvi et al, 1999;Teran et al, 1995). Although providing valuable insight into inflammatory cell and mediator changes in the disease context, they only provide a "snapshot" and are not amenable to detailed mechanistic studies.…”
Section: Pulmonary Epithelium For Drug Developmentmentioning
confidence: 99%
“…Differential cell counts were made from cytocentrifuged preparations (Cytospin 2; Shandon Ltd., Runcorn, Cheshire, UK), stained with Leukostat (Fisher Diagnostics, Pittsburgh, PA). As the number of macrophages, neutrophils, and epithelial cells in bronchoalveolar lavage (BAL) were good indicators of the response to O 3 exposure (27), these cell types were identified by standard hematologic procedures and at least 200 cells counted under 3400 magnification in a blinded manner.…”
Section: Determination Of Cell Numbers In Bronchoalveolar Lavagementioning
confidence: 99%